Strategies of Supervisors and Principals in Improving The Quality of Teachers at State High School 7 Tanjung Jabung Timur Jambi - Fatmawati; Muspawi, Mohamad; Sofwan, Sofwan (Mudir : Jurnal Manajemen Pendidikan, 2024)
All stakeholders in educational institutions, especially teachers during the learning process in the classroom, are responsible for improving teacher quality. Therefore, improving the quality of teachers becomes very important which is influenced by several variables, including the supervisor's strategy and the principal's strategy itself. Based on these problems, the author conducted research on the strategies of supervisors and principals in improving teacher quality at SMA Negeri 7 East Tanjung Jabung Jambi. The principal and vice principal and teachers were the respondents in this study. This research methodology combines qualitative and descriptive approaches. Information was collected by means of observation, discussion and documentation. The findings of this study indicate that the supervisor's strategy in improving the quality of teachers at SMA Negeri 7 Tanjung Jabung Timur Jambi can achieve maximum results in carrying out their role in learning. First, in terms of qualifications, teachers need to have eligibility that is supported by superior and professional qualities. Second, in terms of personality, teachers need to have a high personality, which is based on noble morals. Third, in terms of learning, teachers need to understand the theory and practice of education and curriculum. Fourth, in terms of social, teachers as educators need to have social sensitivity in dealing with social phenomena around them, because teachers are one of the elements of society. The Principal's Strategy in improving the quality of teachers at SMA Negeri 7 Tanjung Jabung Timur Jambi with the strategies that have been taken by the principal of SMA Negeri 7 Tanjung Jabung Timur Jambi who also collaborates with related institutions in improving the quality of teaching staff at SMA Negeri 7 Tanjung Jabung Timur Jambi has competence or quality in accordance with expectations, so as to achieve learning objectives well.